2021
DOI: 10.1097/01.nep.0000000000000777
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Poverty Simulation: Nursing Students’ Perceptions of Poverty

Abstract: The purpose of this study was to evaluate the influence of a poverty simulation on the attitudes of baccalaureate nursing students toward those living in poverty. A single-group pretest-posttest design was used. Participants' attitudes were measured using the Attitude Toward Poverty Scale-Short Form. Results indicated significant improvement in 11 out of 21 items, along with the subscales for stigma and structural perspectives. However, four items, along with the overall personal deficiency domain score, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Both groups of researchers noted improved attitudes scores for sensitivity and understanding of nursing students towards people living in poverty. The Meaux study 16 showed significant improvement in 12 items; the Garrett‐Wright study 17 showed significant improvement in 11 items, with a significant worsening of attitudes toward people living in poverty in four of the 21 items. Still other researchers have experienced great benefit when using the CAPS poverty simulations 18–21 …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Both groups of researchers noted improved attitudes scores for sensitivity and understanding of nursing students towards people living in poverty. The Meaux study 16 showed significant improvement in 12 items; the Garrett‐Wright study 17 showed significant improvement in 11 items, with a significant worsening of attitudes toward people living in poverty in four of the 21 items. Still other researchers have experienced great benefit when using the CAPS poverty simulations 18–21 …”
Section: Introductionmentioning
confidence: 97%
“…Meaux et al 16 and Garrett‐Wright et al 17 both used the CAPS and measured the impact of the simulation by using the 21‐item Attitudes Toward Poverty Scale‐Short Form. Both groups of researchers noted improved attitudes scores for sensitivity and understanding of nursing students towards people living in poverty.…”
Section: Introductionmentioning
confidence: 99%
“…The Poverty Simulation has been proposed as a possible method to influence attitudes and several studies have been conducted using a pretest and posttest design to explore the impact. Many studies have been completed with students in the helping professions: nursing (Ehmke & Sanner-Stiehr, 2020;Garrett-Wright et al, 2021;Noone et al, 2012;Patterson & Hulton, 2012;Turk & Colbert, 2018;Yang et al, 2014), education (Caniglia & Mupinga, 2021), occupational therapy (Bakshi & Jarrad, 2021), dentistry (Lampiris et al, 2017), and medicine (Marrast et al, 2022). Studies have also been conducted with students from more than one discipline, either undergraduates (Cox et al, 2012;Kelty et al, 2020;Kuehn et al, 2020;Vandsburger et al, 2010), graduate students (Ehmke & Sanner-Stiehr, 2020), or mixed undergraduate and graduate students (Hitchcock et al, 2021;Marrast et al, 2022;Strasser et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this respect, it is important to understand the limitations of a poverty simulation for learning about poverty. For example, existing studies (Browne & Roll, 2016; Dudley-Marling, 2015; Garrett-Wright et al, 2021) have not shown improvement in deficit perspectives on those affected by poverty, which can be seen as a testament to the resiliency of participants’ beliefs. Additional evaluations of student attitudes toward poverty following an interactive simulation are needed to further evaluate its effectiveness (Clarke et al, 2016; Menzel et al, 2014).…”
Section: Poverty Simulationsmentioning
confidence: 99%